2021
DOI: 10.2106/jbjs.20.02169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Primary Total Hip and Knee Arthroplasty

Abstract: Background:Enhanced Recovery After Surgery (ERAS) has become increasingly implemented to reduce costs, to increase efficiency, and to optimize patient outcomes after a surgical procedure. This study aimed to systematically review the effect of ERAS after primary elective total hip arthroplasty (THA) or total knee arthroplasty (TKA) on hospital length of stay, total procedure-related morbidity, and readmission.Methods:A systematic review was conducted according to the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 57 publications
2
58
0
Order By: Relevance
“…Patients in both groups received the same treatment, which included an intravenous injection and topical infusion of tranexamic acid [ 12 ]. Postoperatively, both groups adopted the clinical pathway of Enhanced Recovery After Surgery (ERAS) [ 13 ]. Anti-infectives, analgesics and anticoagulants were administered to patients in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in both groups received the same treatment, which included an intravenous injection and topical infusion of tranexamic acid [ 12 ]. Postoperatively, both groups adopted the clinical pathway of Enhanced Recovery After Surgery (ERAS) [ 13 ]. Anti-infectives, analgesics and anticoagulants were administered to patients in both groups.…”
Section: Methodsmentioning
confidence: 99%
“… 4 5 A 2016 systematic review and meta-analysis of ER in total hip arthroplasty (THA) and total knee arthroplasty (TKA) showed significantly reduced LOS without significantly impacting 30-day readmission rates or complication rates. 6 A more recent systematic review and narrative synthesis in 2021 7 of THA and TKA also found that adherence to ER protocols consistently reduced LOS. Moderate confidence in the results of these reviews is suggested using AMSTAR-2 (A MeaSurement Tool to Assess systematic Reviews-2).…”
Section: Introductionmentioning
confidence: 99%
“…10-14 Thus, some studies have investigated pre-operative interventions that aim to optimise THR/TKR outcomes via targeting known modifiable risk factors. 15-17…”
Section: Introductionmentioning
confidence: 99%
“…29 30 A recent systematic review has shown that ERAS protocols significantly reduce the length of hospital stay after THR and TKR, and treatment costs, although the effect on mortality rate remains unclear. 15 However, pre-operative optimisation was not embedded in all included studies and the intervention details (i.e., type, duration, frequency of interventions) were not clearly revealed. Similarly, a recent consensus statement for perioperative care in THR and TKR provided recommendations for pre-operative optimisation but the details of the interventions were absent, 31 and some recommendations (i.e., cessation of alcohol consumption and smoking) were not based on data from fully implemented ERAS for THR/TKR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation